Pengaruh Pendidikan Kesehatan Sadari Menggunakan Media Leaflet terhadap Pengetahuan dan Sikap tentang Deteksi Dini Kanker Payudara pada Remaja Putri - Mayang Citra Hariati; Elvi Era Liesmayani; Frisky Tamara (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Breast cancer (Ca Mammae) is a group of abnormal cells in the breast that continue to grow and multiply in the form of lumps in the breast. In the body there are millions of cells. One of them is abnormal cells or metaplasia cells, which are cells that can change but are still within normal limits. Breast cancer is not a very scary scourge for all women without exception teenagers. One way to detect breast anker is to do a breast self-examination, SADARI is an examination of the breast itself to find lumps in the breasts. Objective: This study aims to determine the Influence of Breast Self-Examination Health Education (SADARI) with Leaflet media on knowledge and attitudes about early detection of breast cancer in adolescent girls in class X at SMAN 16 Medan. Research Method: This study is a Quasy Experimental with the One Group Pretest-Post Test approach with a Proportional Stratified Random Sampling technique with a total of 52 samples. Results of the study: by using the wilcoxon test before and after the provision of health education, the SADARI examination obtained a p value = 0.000 (<0.05). The conclusion is that Ha was accepted and Ho was rejected because there was an influence of breast health education (SADARI) with leaflet media on knowledge and attitudes about early detection of breast cancer in adolescent girls in class X at SMAN 16 Medan.